A neural network approach for short-term water demand forecasting based on a sparse autoencoder. Issue 1 (22nd November 2022) - Huang, Haidong; Lin, Zhenliang; Liu, Shitong; Zhang, Zhixiong
Abstract: This paper presents a backpropagation neural network (BPNN) approach based on the sparse autoencoder (SAE) for short-term water demand forecasting. In this method, the SAE is used as a feature learning method to extract useful information from hourly water demand data in an unsupervised manner. After that, the extracted information is employed to optimize the initial weights and thresholds of the BPNN. In addition, to enhance the effectiveness of the proposed method, data reconstruction is implemented to create suitable samples for the BPNN, and the early stopping method is employed to overcome the BPNN overfitting problem. Data collected from a real-world water distribution system are used to verify the effectiveness of the proposed method, and a comparison with the BPNN and other BPNN-based methods which integrate the BPNN with particle swarm optimization (PSO) and the mind evolutionary algorithm (MEA), respectively, is conducted. The results show that the proposed method can achieve fairly accurate and stable forecasts with a 2.31% mean absolute percentage error (MAPE) and 320 m 3 /h root mean squared error (RMSE). Compared with the BPNN, PSO–BPNN and MEA–BPNN models, the proposed method gains MAPE improvements of 5.80, 3.33 and 3.89%, respectively. In terms of the RMSE, promising improvements (i.e., 5.27, 2.73 and 3.33%, respectively) can be obtained. HIGHLIGHTS: To enhance the performance of the BPNN, the SAE is introduced to extract useful features in an unsupervised manner. An effective framework which integrates the BPNN with the SAE and early stopping technique is proposed for water demand forecasting. The proposed method is verified by comparing with the BPNN and similar methods which integrate the BPNN with PSO and the MEA, respectively.